2009
DOI: 10.1002/jor.21046
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiological response of tendon stem cells: Implications of tendon homeostasis and pathogenesis of tendinopathy

Abstract: Tendons are constantly subjected to mechanical loading in vivo. Recently, stem cells were identified in human, mouse, and rabbit tendons, but the mechanobiological responses of tendon stem cells (TSCs) are still undefined. Using an in vitro system capable of mimicking in vivo loading conditions, it was determined that mechanical stretching increased TSC proliferation in a stretching magnitudedependent manner. Moreover, low mechanical stretching at 4% (''clamp-to-clamp'' engineering strain) promoted differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
191
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(205 citation statements)
references
References 32 publications
10
191
1
3
Order By: Relevance
“…Tissue engineers are incorporating mechanical stimulation to enhance tendon tissue augmentations and replacements [134][135][136][137][138][139][140][141][142][143][144][145][146] . By mechanically preconditioning the tissue-engineered construct cell population prior to in vivo implantation, the cells may be better equipped to enhance the repair since they have been exposed to the appropriate mechanical environment 134,135 .…”
Section: Mechanical Loading In Tissue-engineering Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue engineers are incorporating mechanical stimulation to enhance tendon tissue augmentations and replacements [134][135][136][137][138][139][140][141][142][143][144][145][146] . By mechanically preconditioning the tissue-engineered construct cell population prior to in vivo implantation, the cells may be better equipped to enhance the repair since they have been exposed to the appropriate mechanical environment 134,135 .…”
Section: Mechanical Loading In Tissue-engineering Applicationsmentioning
confidence: 99%
“…Given the importance of physiological loading to maintain tendon homeostasis, investigators have shown that applying load promotes a tendon-like phenotype in both two and threedimensional culture conditions [139][140][141][142][143][144][145][146] . Ralphs et al showed that when tendon cells are cultured on a two-dimensional substrate and subjected to biaxial strain at 1 Hz for eight hours per day for a total of ninety-six hours, cells link together using actin adherens junctions along the principal line of strain to monitor tensile load 142 .…”
Section: Mechanical Loading In Tissue-engineering Applicationsmentioning
confidence: 99%
“…Concluding this analisys of the effects of overuse on tendons, it must be remembered that recent studies found tendon stem cells (TSCs) in human and animal tendon tissue [122,123] . Effects on mechanical loading on TSCs have been investigated on both in vivo and in vitro models [22,124] ; findings from these studies suggest that TSCs undergo loading magnitude-dependent differentiation: under large mechanical stress TSCs differentiate into nontenocytes, such as adipocytes, chondrocyte and osteocytes [125] . Such nontenocyte differentiation may explain the histopathological features of tendinopathy at later stages (tendinosis patterns of degeneration: hypoxic, mucoid or mixoid, hyaline, fatty, fibrinoid, calcific, or some combination of these [58] ).…”
Section: The Role Of Nitric Oxide (No) and Tendon Stem Cells (Tscs)mentioning
confidence: 99%
“…It is not known whether Smad proteins and MSX2 also function to inhibit osteogenic differentiation and promote TDSC tenogenic differentiation, as reported in previous studies [30,32,34]; further study is required. Other factors, such as mechanical loading [35] and local extracellular matrix environment [9], may also function to suppress TDSC osteogenesis inside the tendon midsubstance. For instance, Zhang et al reported that low mechanical stretching promoted tendon stem cell differentiation into tenocytes, whereas large stretching induced differentiation of some tendon stem cells into adipogenic, chondrogenic and osteogenic lineages [35].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, such as mechanical loading [35] and local extracellular matrix environment [9], may also function to suppress TDSC osteogenesis inside the tendon midsubstance. For instance, Zhang et al reported that low mechanical stretching promoted tendon stem cell differentiation into tenocytes, whereas large stretching induced differentiation of some tendon stem cells into adipogenic, chondrogenic and osteogenic lineages [35]. Biglycan and fibromodulin depletion in a double knockout animal model has shown increased TPSC sensitivity to BMP-2 signalling and tendon ossification, suggesting that normal biglycan and fibromodulin levels might have roles in regulating the BMP-2 signalling pathway in TPSCs [9].…”
Section: Discussionmentioning
confidence: 99%